Cyclosporine-induced alopecia:a case report, FDA adverse event reporting system analysis and literature assessment - Wang, Ying; Wang, Youhong; Xu, Ping (Frontiers in Pharmacology, 2024)
Cyclosporine is a potent immunosuppressive drug for various immune-mediated diseases in children. Cyclosporine's expected therapeutic effect also carries a wide range of side effects. One of the most common and intriguing dermatological side effects is hypertrichosis. However, recent reports have recognized alopecia as a potential adverse effect of cyclosporine. Here, we report a case of a 29-month-old boy diagnosed with aplastic anemia. During cyclosporine therapy, the patient presented with hair loss on the scalp, which and subsequently spread to the eyebrows and eyelashes. The alopecic symptoms were not relieved following topical minoxidil liniment interventions. When the cyclosporine was discontinued, a remarkable improvement was observed in the scalp, with complete hair regrowth. Data concerning cyclosporine from the FDA Adverse Event Reporting System (FAERS) database were extracted from January 2004 to January 2023. Within FAERS, our post-marketing pharmacovigilance analysis detected the reporting association of cyclosporine and alopecia. In monotherapy, cyclosporine-induced alopecia was observed in 118 cases, and tacrolimus-induced alopecia signals were detected in 197 cases. Although the potential mechanism of medication-induced hair loss is unclear, we identified a potential correlation between alopecia and cyclosporine, and it is still necessary to adequately recognize and clinically monitor this paradoxical reaction.